1992
DOI: 10.1096/fasebj.6.14.1426768
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoid regulation of phenylethanolamine N ‐methyltransferase in vivo

Abstract: In vivo, supraphysiological doses of glucocorticoids are required to restore adrenal medullary phenylethanolamine N-methyltransferase (PNMT, E.C. 2.1.1.28) activity after hypophysectomy. However, in vitro, phenylethanolamine N-methyltransferase gene expression appears normally glucocorticoid-responsive. To explore this paradox, rats were given dexamethasone or the type II-specific glucocorticoid RU28362 (1-1000 micrograms/day), and adrenal phenylethanolamine N-methyltransferase activity and mRNA levels were de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
47
1

Year Published

2001
2001
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(51 citation statements)
references
References 1 publication
(1 reference statement)
3
47
1
Order By: Relevance
“…Glucocorticoids are important regulators of PNMT gene expression, influencing adrenergic differentiation (Bohn et al, 1981;Teitelman et al, 1982;Bohn, 1983;Michelson and Anderson, 1992;Wong et al, 1992a;Schmid et al, 1995;Ebert et al, 1997) and the induction of PNMT in response to acute and chronic stress (Sabban et al, 1995;Sabban et al, 1998;Serova et al, 1998). Consistent with this role, a functional GRE was identified at Ϫ513 bp in the upstream sequences of the rat PNMT gene when it was first cloned (Ross et al, 1990).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Glucocorticoids are important regulators of PNMT gene expression, influencing adrenergic differentiation (Bohn et al, 1981;Teitelman et al, 1982;Bohn, 1983;Michelson and Anderson, 1992;Wong et al, 1992a;Schmid et al, 1995;Ebert et al, 1997) and the induction of PNMT in response to acute and chronic stress (Sabban et al, 1995;Sabban et al, 1998;Serova et al, 1998). Consistent with this role, a functional GRE was identified at Ϫ513 bp in the upstream sequences of the rat PNMT gene when it was first cloned (Ross et al, 1990).…”
Section: Discussionmentioning
confidence: 91%
“…In vivo studies in rats have shown that depletion of corticosteroids by hypophysectomy decreases PNMT mRNA and enzyme expression (Evinger et al, 1992;Wong et al, 1992aWong et al, , 1996Evinger, 1998). These changes can be reversed by administration of adrenocorticotropin, which stimulates endogenous glucocorticoid production, or direct corticosteroid replacement by administration of the synthetic glucocorticoid dexamethasone.…”
mentioning
confidence: 99%
“…Bidirectional changes in PNMT mRNA and PNMT enzymatic activity can be driven by more subtle perturbations of glucocorticoid levels and by behavioral stress paradigms (Wong et al, 1992;Baruchin et al, 1993;Lemaire et al, 1993;Betito et al, 1994;Wong et al, 1995). Even brief exposure to intense stress and repeated exposure to milder stress can produce lasting changes (Lemaire et al, 1993;Betito et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…One consequence is a precipitous decline in the adrenal transcription of the enzyme phenylethanolamine-Nmethyltransferase (PNMT), which catalyzes the conversion of norepinephrine to epinephrine (Stachowiak et al, 1988;Viskupic et al, 1994). That this reflects a dynamic and bidirectional influence of the HPA on epinephrine synthesis is supported by behavioral experiments (Stachowiak et al, 1988;Wong et al, 1992;Baruchin et al, 1993;Lemaire et al, 1993;Betito et al, 1994;Viskupic et al, 1994;Wong et al, 1995). In parallel with the drop in PNMT transcription, hypophysectomy also alters the relative abundance of two splice variants of Slo (Xie and McCobb, 1998).…”
mentioning
confidence: 99%
“…Furthermore, glucocorticoids levels are very important in the expression of PMNT and thus in the rate of ADR synthesis. Glucocorticoids are very relevant in the size of the stores of ADR available for release in the brain (Moore and Phillipson, 1975b, a), adrenal medulla (Kelner and Pollard, 1985, Stachowiak et al, 1988, Wan and Livett, 1989, Ross et al, 1990, Betito et al, 1992, Wong et al, 1992, heart (Kennedy and Ziegler, 1991, Krizanova et al, 2001, Kvetnansky et al, 2004 or lungs (Kennedy et al, 1993). The activities of both tyrosine hydroxylase and dopaminehydroxylase are also increased in the adrenal medulla under the influence of glucocorticoids (Carroll et al, 1991).…”
Section: Historic Introduction and Backgroundmentioning
confidence: 99%